Reframing domestic violence through a trauma-informed lens: integrative interventions for healing and empowerment - Mihăilă, Maria-Marinela (Technium Social Sciences Journal, 2025)
Domestic violence is a pervasive public health and human rights issue that leaves profound psychological, emotional, and physiological impacts on survivors. Traditional intervention models, often grounded in risk assessment and legal protection, may overlook the complex trauma that underpins victim behavior and response. This paper proposes a trauma-informed approach to domestic violence intervention, emphasizing safety, trustworthiness, empowerment, and relational healing. Drawing on theoretical frameworks such as Herman’s theory of trauma and recovery and SAMHSA’s principles of trauma-informed care, the paper examines how trauma affects survivors’ self-regulation, relational patterns, and help-seeking behavior. Through a narrative review of interdisciplinary literature in social work, psychology, and criminal justice, this study identifies key components of trauma-informed intervention—including collaborative safety planning, survivor-centered counseling, and institutional responsiveness. The findings underscore the importance of culturally responsive, community-based interventions that prioritize emotional safety and avoid re-traumatization. The paper concludes with recommendations for integrating trauma-informed principles into practice, policy, and organizational culture, with particular attention to interprofessional collaboration and systemic reform.